The Trump Carnival : Populism, Transgression and the Far Right. - Gaufman, Elizaveta; Ganesh, Bharath (Berlin/Boston : Walter de Gruyter GmbH, 2024)
De Gruyter Contemporary Social Sciences provides a platform for disseminating topical analyses of current events, showcasing new theoretical, empirical or applied research across the social sciences and related fields. Through engaging storytelling and in-depth analysis, it presents new work that appeals to a wide audience, and engages with issues of major public interest, highlighting the implications for both policy and professional practice.
Intro -- Contents -- Chapter 1: Introduction -- Chapter 2: Populism and Transgression -- Chapter 3: Carnival as Theory and Methodology -- Chapter 4: Trump's Digital Carnival: Media and Multidirectional Discourse -- Chapter 5: Displaced Abjection -- Chapter 6: Laughing Culture -- Chapter 7: Misogyny -- Chapter 8: Sex and Materiality -- Chapter 9: Conclusion -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books